Multifaceted production strategies and applications of glucosamine: a comprehensive review. (2nd January 2023) - Soni, Twinkle; Zhuang, Mengchuan; Kumar, Manish; Balan, Venkatesh; Ubanwa, Bryan; Vivekanand, Vivekanand; Pareek, Nidhi
Abstract: Glucosamine (GlcN) and its derivatives are in high demand and used in various applications such as food, a precursor for the biochemical synthesis of fuels and chemicals, drug delivery, cosmetics, and supplements. The vast number of applications attributed to GlcN has raised its demand, and there is a growing emphasis on developing production methods that are sustainable and economical. Several: physical, chemical, enzymatic, microbial fermentation, recombinant processing methods, and their combinations have been reported to produce GlcN from chitin and chitosan available from different sources, such as animals, plants, and fungi. In addition, genetic manipulation of certain organisms has significantly improved the quality and yield of GlcN compared to conventional processing methods. This review will summarize the chitin and chitosan-degrading enzymes found in various organisms and the expression systems that are widely used to produce GlcN. Furthermore, new developments and methods, including genetic and metabolic engineering of Escherichia coli and Bacillus subtilis to produce high titers of GlcN and GlcNAc will be reviewed. Moreover, other sources of glucosamine production viz. starch and inorganic ammonia will also be discussed. Finally, the conversion of GlcN to fuels and chemicals using catalytic and biochemical conversion will be discussed.